Changing Profile of Cyclones in the Context of Climate Change and Adaptation Strategies in Bangladesh - Saha, Manik Kumar; Khan, Niaz Ahmed (Journal of Bangladesh Institute of Planners, 2014)
Bangladesh - a disaster-prone country of South Asia - is considered to be one of the most vulnerable countries in the world due to the adverse impacts of climate change such as sea level rise, increased salinity intrusion, short term excessive rainfall and extreme heat etc. Apart from direct impact of climate change, it has a long history of confronting with higher levels of tropical cyclones, which is now changing its pattern. It is a poor country with one third of its population living under the poverty line. This poverty scenario is often further exacerbated by the disastrous repercussions of cyclones almost every year jeopardizing the country's development activities. This paper sheds light on the profile of tropical cyclones that have swept Bangladesh over the last five decades. More specifically, it analyze the changing profile of cyclone in terms of frequency of occurrence, intensity, area of landfall, and height of storm surge based on an analysis of official cyclone data of the last 50 years that landfall in Bangladesh. It reveals that though the frequency of cyclone occurrence is reducing but their intensity is increasing day by day. Consequently, based on the analysis and overall observations of the study, the article attempts to furnish some structural, non-structural and policy recommendations both for rural and urban settings. For doing this it focus on the rural and urban adaptations strategies that can fit into the institutional development policy guide line to minimize adverse impact of cyclone in the context of its changing profile. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 63-78